PENERAPAN KONSEP CUSTOMER RELATIONSHIP MANAGEMENT DALAM MEMBANGUN BRANDING CATERING KOTA PADANG - Mutiana Pratiwi; Widia Marta (STMIK Budi Darma, 2018)
Small micro business is a business that is very helpful in various aspects of the Indonesian economy. In Padang city has various types of SME businesses. One of them is Catering. The development of catering business in this city is very rapid because of the many interests of the community to use these services. As a result, competition arises between businesses which shows a significant impact on the catering business so that each of these businesses must be able to create their own market by creating a Brand for their catering business. The purpose of this study is to analyze the system to create E-Branding with the concept of CRM (Customer Relationship Management). The results of this study are the creation of E-Branding Catering, which has benefits as a form of actualizing the character of SME Catering businesses and supporting marketing and increasing competitiveness.Keywords: Brands, customer releationship management, Catering, small medium enterprise, e-branding